Optimal Operation Strategy of Community Integrated Energy System Based on a Two-level Game - Wang, Qinglin; Niu, Huanna (Journal of physics. Conference series, 2023)
With the gradual transformation of the integrated energy system to intelligence and decentralization, users with distributed generation gradually replace traditional users. To realize the rationality of multi-agent power transactions in a community-integrated energy system and improve the income of each subject in the system, this paper presents the optimal operation strategy of a community-integrated energy system based on the two-level game. The first layer is a cooperative game between energy communities, which can promote the consumption of new energy in communities. The second layer is a master-slave game between operators and communities, which can promote effective interaction between the upper and lower levels. By using the Karush-Kuhn-Tucker condition, the two-layer model is transformed into a single-layer model and uses McCormick to relax the model. The example verifies that the trading strategy proposed in this paper can effectively improve the benefits of each energy community.